Essential cardiology : principles and practice - Rosendorff, Clive (Springer, 2013)
This book blends molecular, cellular, and physiologic concepts with current clinical practice and provides up-to-date information on the major aspects of cardiovascular disease. It covers recent rapid advances in anti-platelet and anti-coagulant therapy, the latest treatment protocols for new anti-arrhythmic drugs, and discusses new and existing modalities of cardiac imaging.